Catalytic performance of strontium oxide supported by MIL–100(Fe) derivate as transesterification catalyst for biodiesel production. (15th January 2019) - Li, Hui; Liu, Fengsheng; Ma, Xiaoling; Wu, Zhongjie; Li, Yan; Zhang, Linhua; Zhou, Shoujun; Helian, Yaxin
Highlights: Reusability of SrO used in transesterification is enhanced by MIL-100(Fe) derivate. Catalytic activity of MM-SrO and ST-SrO is mainly affected by the strong basicity. MM method is suitable to prepare catalyst of SrO supported by MIL-100(Fe) derivate. MM-SrO precursor exhibits the multistage character during the thermal activation. Abstract: Strontium oxide (SrO) is restricted by poor reusability and pore structure in catalyzing transesterification for biodiesel production. To address this problem, metal organic frameworks is employed as a carrier to support strontium carbonate by mechanical mixing method (MM) and in situ titration method (ST), and then calcined under inert atmosphere to obtain the catalyst of MM–SrO and ST–SrO. As a comparison, the reusability of pure SrO is compared and the homogeneous contribution of leached active sites for ST–SrO and MM–SrO are also assessed. The catalysts are characterized by TG, XRD, FTIR, EDS, Hammett indicator titration, nitrogen adsorption–desorption, and VSM. From the catalyst reusability, MM–SrO exhibits the excellent performance, where the maximum conversion of 96.19% is achieved at molar ratio of methanol to oil 12, catalyst addition 8 wt% (refer to oil), reaction temperature 65 °C within 30 min. And the conversion of 82.49% is still obtained at the third cycle, which could be easily separated from the mixture by external magnetic field after each cycle as well. In order to optimize the activation condition and investigate MM–SrO deeply, thermal characteristics of its corresponding precursor are further evaluated, where the TG experiments are conducted at heating rate of 20, 30, and 40 °C/min. and kinetic parameters are calculated through model–free method and Avrami theory, respectively.